(untitled) (Revista Iberoamericana de Bioética, 2021)
The concept of emotional intelligence has gained prominence in recent years. Thus, its influence and application in different processes such as decision making, have been investigated. Personal bioethical decisions involve emotions of great intensity, therefore emotional intelligence becomes an indispensable tool for us to correctly manage the emotional process and thus be as free and autonomous as possible in our decisions.